Design and development of intraocular polymeric implant systems for long-term controlled-release of clindamycin phosphate for toxoplasmic retinochoroiditis - Lana Tamaddon; S Abolfazl Mostafavi; Reza Karkhane; Mohammad Riazi-Esfahani; Farid Abedin Dorkoosh; Morteza Rafiee-Tehrani (Advanced Biomedical Research, 2015)
Background: The release of the anti-toxoplasmosis drug, clindamycin phosphate, from intraocular implants of the biodegradable polymers poly (D, L-lactic acid) (PLA) and poly (D, L-lactide-co-glycolide) (PLGA) has been studied in vitro. Materials and Methods: The preparation of the implants was performed by a melt-extrusion method. The developed extrudates were characterized and compared in in-vitro release profiles for elucidating the drug release mechanism. The formulations containing up to 40% w/w of drug were prepared. Release data in phosphate buffer (pH 7.4) were analyzed by high performance liquid chromatography. The release kinetics were fitted to the zero-order, Higuchi′s square-root, first order and the Korsmeyer-Peppas empirical equations for the estimation of various parameters of the drug release curves. Degradation of implants was also investigated morphologically with time (Scanning Electron Microscopy). Results: It was observed that, the release profiles for the formulations exhibit a typical biphasic profile for bulk-eroding systems, characterized by a first phase of burst release (in first 24 hrs), followed by a phase of slower release. The duration of the secondary phase was found to be proportional to the molecular weight and monomer ratio of copolymers and also polymer-to-drug ratios. It was confirmed that Higuchi and first-order kinetics were the predominant release mechanisms than zero order kinetic. The Korsmeyer-Peppas exponent (n) ranged between 0.10 and 0.96. This value, confirmed fickian as the dominant mechanism for PLA formulations (n ≤ 0.45) and the anomalous mechanism, for PLGAs (0.45 < n < 0.90). Conclusion: The implant of PLA (I.V. 0.2) containing 20% w/w of clindamycin, was identified as the optimum formulation in providing continuous efficient in-vitro release of clindamycin for about 5 weeks.